2019
DOI: 10.2169/internalmedicine.2328-18
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease with Anti-melanoma Differentiation-associated Protein 5 Antibody: Rapidly Progressive Perilobular Opacity

Abstract: Objective Rapidly progressive interstitial lung disease (RP-ILD) with anti-melanoma differentiation-associated protein 5 (MDA5) antibody potentially presents with a fatal clinical course and requires early intensive treatment. Recently, perilobular opacity was reported to pathologically correspond to the acute phase of diffuse alveolar damage in RP-ILD with anti-MDA5 antibody. We aimed to investigate whether or not perilobular opacity was a common radiological finding in RP-ILD patients with anti-MDA5 antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Of note, in the population of MDA5 + DM-ILD, the organizing pneumonia pattern was found to be dominant in HRCT, with lower zone consolidation correlating with rapidly progressive ILD ( 28 ). Moreover, another study with pathological evidences discovered that a perilobular opacity transforming to consolidation corresponded to diffuse alveolar damage, which was presented as the main finding in MDA5 + DM associated with rapidly progressive ILD ( 29 ). Thus, these manifestations might result in the changes of CT values and texture, making these radiomic features important for diagnosis, risk stratification, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in the population of MDA5 + DM-ILD, the organizing pneumonia pattern was found to be dominant in HRCT, with lower zone consolidation correlating with rapidly progressive ILD ( 28 ). Moreover, another study with pathological evidences discovered that a perilobular opacity transforming to consolidation corresponded to diffuse alveolar damage, which was presented as the main finding in MDA5 + DM associated with rapidly progressive ILD ( 29 ). Thus, these manifestations might result in the changes of CT values and texture, making these radiomic features important for diagnosis, risk stratification, and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological findings of anti-MDA5 antibody-positive ILD were also reported. In most of the reported cases, autopsy was performed, and the pathological pattern of ILD was that of diffuse alveolar damage [ [17] , [18] , [19] ]. Chino et al reported a patient with anti-MDA5 antibody-positive ILD who underwent SLB.…”
Section: Discussionmentioning
confidence: 99%
“…ILD is common in myositis, especially in patients with antibodies directed against different aminoacyl-tRNA synthetases, a group collectively called the antisynthetase syndrome (ASyS), but also those with anti-Ro52 antibodies ( 5 , 6 ). Anti-MDA5 antibodies are associated with clinically amyopathic dermatomyositis (CADM) which can present as a rapidly progressive ILD with high mortality despite aggressive immunosuppressive therapy ( 7 ). The following summarizes the papers publishes within this Research Topic.…”
Section: Frequently Encountered Ilds Associated With Systemic Diseasementioning
confidence: 99%